MARINE SCIENCE AND TECHNOLOGY IN VIETNAM - CURRENT SITUATION AND DEVELOPMENT DEMAND FOR INTEGRATION PERIOD - Thanh, Tran Duc; Que, Bui Cong; Lan, Tran Dinh (Vietnam Journal of Marine Science and Technology, 2014)
In the last years, marine science and technology activities in Vietnam have achieved significant success and remarkably contributed to social - economic development, protection of natural resources and the environment, ensuring national security, sovereignty and benefits at sea. However, these results are limited by the inconsiderable experts, limited qualification; poor and backward equipment for survey and research; confusing development strategies; low investment; and inadequate management. During the integration, international cooperation in marine science and technology is demanded urgently, not only in the benefits of science and economics, but also in active contribution to ensure and protect sovereignty and national benefits at sea. To get equal cooperation and mutual benefit, Vietnam also needs to build a solid foundation of powers and policy for marine science and technology with the appropriate solutions such as: establishing the rightly directed strategy; implementing policy priorities; building capability and capacity (human resources and equipment); promoting researches in key and priority fields; strengthening and diversifying the manners of international cooperation; enhancing communication, publication and publishing.